Women on the Web - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Synergy Gender and Development. Environment and Development of the Third World, ENDA SYNFEV, B P 3370, Dakar Senegal fax + 221 822 2695 Email: famafrique@enda.sn ISIS International, PO Box 1837, Quezon City Main, 1100 Quezon City, Philippines